Impact of Covid 19 Induced Conditions on the Consumer Behavior on A Short, Mid and Long Term, for Consumption of Services - Joshi, Shripad; Brahme, Mandar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The covid-19 pandemic has demonstrated the interconnected and quiet picture of the nation with humans without their human touch – and that no one is safe until everyone is safe. With this pandemic different changes taken place and after fighting and juggling with it for around 4 months, consumers accepted the fact “this is new normal”. But this pandemic affected as well as changed the pattern of consumer behavior in so many ways be it behavioral change or psychological change. As the current situation made us all come across a lot of newness and to study that change in consumer behavior, my internship was an attempt to do a research on the impact of Covid19 induced conditions on the consumer behavior on a short, mid and long term impact for consumption of services. This research was taken out to understand the same in better way. In the tenure of two months of my internship was to carry out a detailed analysis of consumer behavior in terms of services and their impact. This project’s primary objective was to perform set of task in order to study different psychological changes taking place in consumer for achieving the same I have giving following task which needs to be followed in the mentioned sequence itself. The tasks were mainly divided into five sets: 1. Background study and collection of information related to covid-19. 2. Preparation of questionnaire on the basis of study. 3. Primary data collection from respondent (min.300) on telephonic interview. 4. Analysis of data and key findings 5. Formation of report on the collected information This market research was carried out with constraint, provided from the external mentor in terms of the selection of respondent. Covid-19 made a great impact on the consumer behavior in just a course of few months as few restrictions were imposed on the Indian citizen by the government of India to make sure health and safety of the people. This study in only recited to consumer of India who reside in India itself for a focused study and targeted group of people. Alongside this there was great learning regarding some technical knowledge like working on excel and analysis of the respondent’s response.